(3eLeY GdZQGFH hefHY GdQZGFHs - (3CHh GdMSf YHO GdZGaQ Hf ESeGYjd Hf YHO GdZGaQ GdaGQSjs
(3ChdgG (B:s
(3CeG HYO , aEf Chdi eG jUQa GdEfSGf geg Edjg cJGH Gddg GdYRjR hJJdhg GdG;GOjK GdeQhjI Yf GdfHi Udi Gddg Ydjg hSde hbO cGf jOhQ ai GdNdO efP eOg eOjOg s
(3BNQgG (B:s
(3hgh Ydi hRf aYjd cJGHI ai GdCUhGJ fMh GdUgjd hGdagjK hGdaMjMhGdcTjT hHGHg Je GdLRA GdChd ef eLeY GdZQGFH jJdhg ai GdKGfi aUd GdOGd eY GdgGA s
(3GdfSNI HgG MhGTs
(3QJHg Ydi MQha GdgLGAs
(3YhQVJ HGdCUd GdPi HNW CHj GdMSf Ydi Hf SdjeGf Hf CMeO GdeQGOi GdPi YhQV HCUd GdeUfa hUM UMJgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1602s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs